Invalid Self-Assessment of Olfactory Functioning in Parkinson's Disease Patients May Mislead the Neurologist. (16th November 2020) - Schmidt, Nele; Paschen, Laura; Witt, Karsten
Abstract : Olfactory dysfunction (OD) is a prominent nonmotor symptom in Parkinson's disease (PD), and OD is a supportive diagnostic criterion for PD. Physicians often ask their patients if they have noticed a smell disorder. This study evaluates the diagnostic validity of OD self-assessment in PD. To this end, 64 PD patients and 33 age-matched healthy controls were enrolled in a study assessing subjective and objective olfactory functioning. To examine subjective olfactory abilities, first, patients and controls had to classify their olfactory sense as "impaired" or "unimpaired, " comparable to a realistic situation in an outpatient setting. Second, to evaluate subjective olfactory acuity, a visual analogue scale (VAS) was used. Third, the Sniffin' Sticks test battery was used as an objective instrument to diagnose OD. Categorical olfactory self-assessment predicts the classification normosmic versus hyposmic based on the global Sniffin' Sticks score (TDI) with a sensitivity of 0.79 and a specificity of 0.45. TDI correlated significantly with the VAS ( r  = 0.297, p = 0.017 ). The ROC curve analysis, using the VAS rating as a predictor for objective olfaction, revealed 42 as the best possible cutoff score with an area under the curve of 0.63. These results demonstrate that olfactory self-assessments show a low accuracy and are not suitable for the diagnosis of a smell disorder in PD. Objective measures are necessary to evaluate olfactory sense in clinical and research settings.